(untitled) (Research, Society and Development, 2022)
Most lipases used for commercial purposes are isolated from microorganisms due to their stability and easy recovery, new residues have been studied to obtain enzymes to reduce production costs. Therefore, this work investigated the biotechnological potential of filamentous fungi isolated from the Igarassu River in the conversion of coffee grounds into lipase in solid state fermentation. The fungi were isolated, identified and submitted to a preliminary assay with 10g of coffee grounds, moisture 60% at 28 °C for 144 h to select the filamentous fungus with the highest potential for lipase production. A factorial design of 23 was carried out to evaluate the influence of the variables moisture, temperature and residue concentration on lipase production by the selected species. Five filamentous fungi were isolated and identified: A. flavus UCP 0316, A. fumigatus UCP 0327, P. variotii UCP 0334, M. hiemalis f. luteis UCP 0343 and A. foetidus UCP 0360. All filamentous fungi cultivated on coffee grounds were able to grow and produce lipase, however A. foetidus exhibited higher enzymatic activity of 514.29 U/mL. We observed that the production of lipase was higher (2941.87 U/mL) when A. foetidus was cultivated in 25 g of coffee grounds, 37 °C and 50% moisture. Therefore, we emphasize that coffee grounds are a promising agro-industrial residue to lipase production, contributing to the reduction of environmental pollution and generating value-added products for the industry.